2022
DOI: 10.3390/ph15010105
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Year Study of Lithium and Valproic Acid Drug Monitoring in Patients with Bipolar Disorders in an Italian Clinical Center

Abstract: Therapeutic drug monitoring (TDM) is an effective tool used to improve the pharmacological treatment in clinical practice, especially to detect subtherapeutic drug plasma concentration (Cp) in order to consider a change of dosage during treatment and reach its putative therapeutic range. In this study, we report the Cp values of lithium and valproic acid (VPA), alone and in combination, mostly in bipolar patients admitted to an Italian clinical center of the University of Pisa during the years 2016–2020, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…However, its serious adverse effects impose a constant monitoring of patient’s conditions, including C(p) measuring [ 7 ]. VPA utilization has become a standard approach for treating particular categories of bipolar disorders, such as mixed states, rapid cycling, and with anxiety in comorbidity [ 40 ]. In addition, VPA can be also used in migraine; however, data of TDM for this medical condition are still missing, so we can assume that in our sample, it was less represented [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its serious adverse effects impose a constant monitoring of patient’s conditions, including C(p) measuring [ 7 ]. VPA utilization has become a standard approach for treating particular categories of bipolar disorders, such as mixed states, rapid cycling, and with anxiety in comorbidity [ 40 ]. In addition, VPA can be also used in migraine; however, data of TDM for this medical condition are still missing, so we can assume that in our sample, it was less represented [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have shown that lithium monitoring is often underused, despite the existing recommendations [50,51], even though, in some instances, the importance of regular TDM has been acknowledged by clinicians, with promising results in terms of ADR prevalence [52]. In other cases, while TDM seems correctly used in terms of frequency, it does not induce the clinician to adjust lithium dosages in the case of suboptimal plasma levels, possibly due to concerns about ADRs [45,[53][54][55].…”
Section: Tdm and Mood Stabilizersmentioning
confidence: 99%
“…Despite its proven benefits, valproate TDM is still an underused or misused tool for the clinician: some studies show low frequency of monitoring, while others show that valproate levels are often found underdosed or at the lowest-end limits in patients with mood disorders, which could either indicate a low adherence to therapy, or the use of low dosages by clinicians for the treatment of psychiatric disorders [55,[65][66][67][68].…”
Section: Tdm and Mood Stabilizersmentioning
confidence: 99%
“…Considering that Lithium usually is administrated for many years or throughout the whole patient’s life, its harmful adverse effect on thyroid and kidney function has to be constantly monitored and it can be reduced through Lithium plasma monitoring [ 51 , 52 ]. Particularly, this latter adverse effect limits its use in patients with significant renal impairment.…”
Section: Lithiummentioning
confidence: 99%